Analisis Manajemen Kredit Guna Menekan Terjadinya Kredit Bermasalah Dalam Pelaksanaan Program Kemitraan Pada Pt.Telekomunikasi Indonesia (Studi Kasus Di Community Development Sub Area Malang) - Leila Melati Mukhlishah; Djuma hir (Jurnal Ilmiah Mahasiswa FEB, 2012)
PT.Telekomunikasi Indonesia is one of a BUMN Company. The purpose of the research  is to investigate the implementation of Partnership Program is one of the corporate social responsibility programs which is managed by PT. Telekomunikasi Indonesia Sub Area Malang in helping small businesses. Funding for this program comes from  1-3% net profit. PT.Telekomunikasi Indonesia form a Community Development (CD) to manage a parternship programe in their company. The results of this study indicate that credit management used at CD PT.Telekomunikasi Indonesia Sub Area Malang in managing credits are credit planning, organizing, actuating and controlling. In other hand, the cooperation also conducts 5C analysist including character, capacity, capital, collateral and condition of economic to minimize and depress the risks of bad debt. . Keywords: credit management, partnership programe, bad debt